Hubungan andropause dengan skor IPSS pada pegawai di institusi pusat pemerintahan Kabupaten Badung-Bali - Assuncao Caviota Da Silva Pinto; Yukhi Kurniawan; I Gusti Ngurah Pramesemara (DiscoverSys Inc., 2021)
Background: Andropause is a term which indicate reduced male testosterone levels. The mechanism of andropause is due to decreased male reproductive function which results in decreased levels of testosterone in the blood below normal levels. On the other hand, almost 50% of men aged 45-60 years experience complaints of urination due to Benign Prostate Hyperplasia (BPH). Until now, BPH is believed to be related to the aging process and decreased levels of the hormone testosterone or andropause. However, no clear evidence indicate a relathionship between andropause and severe micturition probelm. This study aims to determine the relathionship of andropause and the IPSS score.Methods: This study is an analytic observational study with a cross sectional method. Sampling in this study using purposive sampling with respondent taken from the Central Government Institution of Badung Regency, Bali. The total number of research respondents was 40 man. Symptoms and signs of andropause were evaluated using the Androgen Deficiency in the Aging Male (ADAM) questionnaire, while the degree of symptoms of micturition was determined by the International Prostate Symptom Score (IPSS). The data was analyze descriptively and analytically with Chi-square to determine the relationship between andropause status and the degree of micturition problem.Results: Complaints of moderate micturition problem were the most common complaint in andropause respondents (45.5%) while mild complaints were the most common among respondents who did not experience andropause (72.2%). The results showed a significant relationship between respondents who experienced andropause and the tendency to complain of symptoms of obstruction due to prostate enlargement as assessed by the IPSS score (p = 0.038).Conclusion: There is a significant relationship between respondents experiencing andropause and the tendency to complain of symptoms of obstruction due to prostate enlargement. Pendahuluan: Andropause merupakan suatu istilah yang berarti menurunnya kadar hormon testosteron pada laki-laki. Mekanisme terjadinya andropause adalah karena menurunnya fungsi reproduksi laki-laki yang berakibat menurunnya kadar testosteron dalam darah dibawah angka normal. Disisi lain, laki-laki usia 45-60 tahun hampir 50% mengalami keluhan miksi akibat Benign Prostate Hyperplasia (BPH). BPH hingga saat ini diyakini berhubungan dengan proses penuaan dan penuruan kadar hormon testosteron atau andropause. Akan tetapi belum banyak bukti menunjukan hubungan andropause dengan beratnya gangguan miksi akibat BPH. Penelitian ini bertujuan untuk mengetahui hubungan status andropause dengan skor IPSS.Metode: Penelitian ini merupakan penelitian observasional analitik dengan metode potong lintang. Pengambilan sampel pada penelitian ini menggunakan purposive sampling dengan responden diambil dari Institusi Pusat Pemerintah Kabupaten Badung, Bali. Keseluruhan responden penelitian berjumlah 40 orang. Gejala dan tanda andropause dievaluasi dengan kuisioner Androgen Deficiency in the Aging Male (ADAM) sedangkan derajat gejala gangguan miksi ditetukan dengan skor International Prostate Symptom Score (IPSS). Analisis data berupa deskriptif serta analitik dengan Chi-square untuk menentukan hubungan status andropause dengan derajat gangguan miksi.Hasil: Keluhan gangguan miksi derajat sedang merupakan tingkat keluhan paling umum pada responden andropause (45,5%) sedangkan keluhan ringan merupakan keluhan paling umum pada responden tidak mengalami andropause (72,2%). Hasil penelitian menunjukkan hubungan yang signifikan antara responden yang mengalami andropause dan kecenderungan mengeluhkan gejala obstruksi akibat pembesaran prostat yang dinilai melalui Skor IPSS (p=0,038).Simpulan: Terdapat hubungan yang signifikan antara responden yang mengalami andropause dan kecenderungan mengeluhkan gejala obstruksi akibat pembesaran prostat.